Emissive oxidase-like nanozyme based on an organic molecular cage. Issue 87 (19th October 2021) - Wang, Zhen; Yang, Bin-Bin; Fang, Zi-Jun; Ou, Qiang; Ma, Hui; Zhang, Qing-Pu; Sun, Yu-Ling; Zhang, Chun
Abstract : An oxidase-like nano-enzyme organic molecular cage (ZnDPA-TPE-Cage), possessing aggregation-induced enhancement effect and high ROS generation ability, can selectively image and kill Gram-positive S. aureus simultaneously. Abstract : In this study, we introduced four "claw-like" units of dipicolylamine (DPA) to a tetraphenylethylene (TPE)-based organic molecular cage (DPA-TPE-Cage). Coordinated with Zn 2+ ions, the obtained ZnDPA-TPE-Cage exhibited aggregation induced emission (AIE) effects and oxidase-like properties, which endowed it with the ability to selectively image and kill Gram-positive bacteria S. aureus efficiently.